Contrasting nonphotochemical quenching patterns under high light and darkness aligns with light niche occupancy in Arctic diatoms. Issue Volume 66:Issue S1(2021) Supplement (2nd September 2020) - Croteau, Dany; Guérin, Sébastien; Bruyant, Flavienne; Ferland, Joannie; Campbell, Douglas A.; Babin, Marcel; Lavaud, Johann
Abstract: Over the seasons, Arctic diatom species occupy shifting habitats defined by contrasting light climates, constrained by snow and ice cover dynamics interacting with extreme photoperiod and solar angle variations. How Arctic diatom photoadaptation strategies differ across their heterogeneous light niches remains a poorly documented but crucial missing link to anticipate Arctic Ocean responses to shrinking sea‐ice and increasing light. To address this question, we selected five Arctic diatom species with diverse life traits, representative of distinct light niches across the seasonal light environment continuum: from snow‐covered dimly lit bottom ice to summer stratified waters. We studied their photoacclimation plasticity to two growth light levels and the subsequent responses of their nonphotochemical quenching (NPQ) and xanthophyll cycle to both dark incubations and light shifts. We deciphered NPQ and xanthophyll cycle tuning in darkness and their light‐dependent induction kinetics, which aligned with species' light niche occupancy. In ice‐related species, NPQ was sustained in darkness and its induction was more reactive to moderate light shifts. Open‐water species triggered strong NPQ induction in darkness and reached higher maximal NPQ under high light. Marginal ice zone species showed strong adaptation to light fluctuations with a dark response fine‐tuned depending upon light history. We argue these traits are anchored in diverging photoadaption strategies fostering Arctic diatom success in their respective light niches.